Penerapan Metode Permainan Digital Pada Pembelajaran IPS Di Era Abad 21 - Anggita Citra, Ririn; Farhurohman, Oman (PGMI IAIN Lhokseumawe, 2023)
This exploration expects to decide the utilization of computerized game techniques in friendly examinations learning in the 21st century time. The examination technique utilized is subjective. The information assortment strategy is writing concentrate via looking for information from composed sources that have been made already by means of Google Researcher, past articles. From the conversations that have been done, this specialist got the outcomes that social investigations picking up utilizing advanced game techniques is an elective learning way to deal with answer the difficulties of the 21st hundred years. Instructive game learning in friendly examinations subjects makes sense of the development of social investigations learning in the 21st hundred years by utilizing the utilization of game strategies. advanced in 21st century learning. This article likewise examines the utilization of computerized game techniques, game strategies joined by supporting and repressing elements so we can comprehend the significance of computerized game-based learning in advancing viable learning and feature its part in forming an imaginative and creative future in this really long period. to 21